2011
DOI: 10.1007/s00280-011-1570-7
|View full text |Cite
|
Sign up to set email alerts
|

Bi-weekly docetaxel and gemcitabine regimen in her-2-negative and anthracycline-pretreated metastatic breast cancer patients: a multicenter phase II trial

Abstract: The GD bi-weekly regimen is well tolerated and active as first line in anthracyclines-pretreated women with MBC. It appears as an interesting alternative compared to a 3-week schedule whenever hematological toxicity is the main clinical concern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Murialdo et al [31] recently reported a phase II trial of biweekly docetaxel and gemcitabine regimen in HER2-negative and anthracycline-pretreated MBC, which showed that this schedule of administration is well tolerated and active as first line in anthracycline-pretreated women with MBC. Further investigation into phase III studies is required.…”
Section: Discussionmentioning
confidence: 96%
“…Murialdo et al [31] recently reported a phase II trial of biweekly docetaxel and gemcitabine regimen in HER2-negative and anthracycline-pretreated MBC, which showed that this schedule of administration is well tolerated and active as first line in anthracycline-pretreated women with MBC. Further investigation into phase III studies is required.…”
Section: Discussionmentioning
confidence: 96%